2011
DOI: 10.1097/inf.0b013e318218181d
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids in the Treatment of Severe Nocardia Pneumonia in Chronic Granulomatous Disease

Abstract: Nocardia is one of five main pathogens that infect chronic granulomatous disease (CGD) patients. Despite aggressive antimicrobial therapy, medical treatment is not always successful and surgical resection of infected tissue has been intermittently required. We present two CGD patients with severe Nocardia pneumonia whose pulmonary status worsened despite appropriate antimicrobials, but then improved clinically and radiographically with the addition of corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 11 publications
3
13
0
4
Order By: Relevance
“…However, corticosteroids have also been used in addition to antimicrobials to treat refractory infections in CGD, and they are able to suppress inflammation in MAS [22,23]. It is important to note that microbiologic diagnosis is essential to rule out antibiotic failure [23]. This aspect is important because corticosteroids and immunosuppressants can exacerbate infection if the patient is without optimal antimicrobial coverage [22,23].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, corticosteroids have also been used in addition to antimicrobials to treat refractory infections in CGD, and they are able to suppress inflammation in MAS [22,23]. It is important to note that microbiologic diagnosis is essential to rule out antibiotic failure [23]. This aspect is important because corticosteroids and immunosuppressants can exacerbate infection if the patient is without optimal antimicrobial coverage [22,23].…”
Section: Discussionmentioning
confidence: 98%
“…It is important to note that microbiologic diagnosis is essential to rule out antibiotic failure [23]. This aspect is important because corticosteroids and immunosuppressants can exacerbate infection if the patient is without optimal antimicrobial coverage [22,23]. On the other hand, experts suggest that there has to be a balance between halting progressing microbial infection and controlling damaging inflammation in CGD [20].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nocardiosis, however, requires long term treatment. Sometimes, surgical intervention or even unusual measures such as additional treatment with corticosteroids are necessary for management [12].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of pneumonitis and liver abscess in CGD patients suggested the effectiveness of steroid in conjunction with appropriate antimicrobials to alleviate the excessive inflammation related to infections. 1,5,6 In a retrospective study of adult CGD with pulmonary manifestations, 40% of the cases included inflammatory events induced after the infection, which were most often treated with immunomodulative therapies. 7 In our patient, topical steroid used in conjunction with systemic antibiotics treatment greatly contributed to improving the CGD-associated skin ulcer, without major adverse events.…”
Section: Doi: 101111/jdv16290mentioning
confidence: 99%